Carbonized rice husk coated solar absorber for clean water generation from seawater with a solar still. Issue 3 (28th January 2023) - Karen, Wong Min Jin; Wong, C. Y.; Wang, Zhipeng; Liew, Willey Y. H.; Melvin, G. J. H.
ABSTRACT: This study demonstrated the generation of clean water from seawater collected at the beach coast in Universiti Malaysia Sabah, Malaysia, with carbonized rice husk coated melamine sponge as solar absorber by a solar still. Melamine sponge was utilized as a seawater transportation medium since its porous structure is excellent in channelling the seawater. Whereas carbonized rice husk was used as the photothermal conversion material for its efficient heat absorption due to its black colour and porous structure. Implementing air gap between the seawater body and solar absorber, and restricted water pathway assisted in localizing heat on the top surface of the solar absorber. Clean water was generated under direct solar radiation during the day at an open space with average solar intensity around 1.1∼1.2 kW/m 2 (slightly higher than 1 sun) for about 4 h. Efficiency of the solar absorber was calculated, while the quality of the generated clean water was observed in terms of salinity and pH value. Insulated solar still with carbon-coated sponge showed the highest efficiency at about 54.74%. Salinity of the collected clean water significantly reduced to consumable level which was approximately 55 ppm, and the pH value at about 6.73 where it was within the safe limit of the drinkable water pH. GRAPHICAL ABSTRACT: UF0001